2011
DOI: 10.1371/journal.pone.0019797
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Chaperone Hfq Is Important for Growth and Stress Tolerance in Francisella novicida

Abstract: The RNA-binding protein Hfq is recognized as an important regulatory factor in a variety of cellular processes, including stress resistance and pathogenesis. Hfq has been shown in several bacteria to interact with small regulatory RNAs and act as a post-transcriptional regulator of mRNA stability and translation. Here we examined the impact of Hfq on growth, stress tolerance, and gene expression in the intracellular pathogen Francisella novicida. We present evidence of Hfq involvement in the ability of F. novi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Biofilm formation could be an important factor in the infection process contributing to persistence and to the high incidence of clinical relapse (31,90). Hfq depletion increased C. difficile biofilm formation, as observed for hfq mutants of Francisella novicida and Moraxella catarrhalis (91,92). Interestingly, the expression of genes encoding cell wall-associated proteins and of sinR (CD2214) encoding an orthologue of the master biofilm regulator in B. subtilis (69) is induced in the Hfq-depleted strain.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Biofilm formation could be an important factor in the infection process contributing to persistence and to the high incidence of clinical relapse (31,90). Hfq depletion increased C. difficile biofilm formation, as observed for hfq mutants of Francisella novicida and Moraxella catarrhalis (91,92). Interestingly, the expression of genes encoding cell wall-associated proteins and of sinR (CD2214) encoding an orthologue of the master biofilm regulator in B. subtilis (69) is induced in the Hfq-depleted strain.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, a diguanylate cyclase (CD2887) and a phosphodiesterase (CD1616), involved in the turnover of c-di-GMP, a key molecule modulating cellular processes associated with community behavior, are inversely regulated when the Hfq level drops, suggesting that Hfq might influence c-di-GMP accumulation. Both Hfq and sRNAs participate in the regulatory networks controlling bacterial biofilms (14,17,(91)(92)(93). In E. coli and other enteric bacteria, Hfq-dependent sRNAs contribute to inverse regulation of the synthesis of flagella and biofilm matrix components during the transition to stationary phase (94)(95)(96)(97).…”
Section: Discussionmentioning
confidence: 99%
“…A reducedvirulence phenotype in hfq mutants was also commonly observed in other Gram-negative pathogens, including Brucella abortus, Francisella tularensis, Neisseria meningitidis, Pseudomonas aeruginosa, and Yersinia pestis, and in the Gram-positive pathogen Listeria monocytogenes (28). Although Hfq has been implicated in controlling virulence in many bacterial pathogens, the regulatory targets of Hfq vary among species, from regulation of the T3SS (31,32) and stress tolerance (33,34) to biofilm formation (35). In some cases, the regulatory function of Hfq is still not clear (28).…”
mentioning
confidence: 87%
“…It has been reported that the functions of Hfq focus mainly on growth-dependent metabolism, resistance to stress, modulation of virulence and drug resistance [14,17e20]. For example, in Francisella novicida, Hfq was found to have a role in the stress response to osmotic changes, low pH, heat shock and oxidative stress [21]. The Hfq protein of enterohemorrhagic E. coli (EHEC) had an impact on virulence, cell growth and acid stress processes [22].…”
Section: Introductionmentioning
confidence: 99%